Charge carrier mobility in semiconductor solid solutions and percolation phenomena - Rogacheva, E. I.; Nashchekina, O. N.; Martynova, E. V. (My University, 2017)
The existence of a range of an anomalous growth in charge carrier mobility under the transition to heavy doping is established for Bi₂Te₃–Sb₂Te₃ solid solutions. This confirms our suggestion about the universal character of critical phenomena accompanying the transition from impurity discontinuum to impurity continuum. The experimental results are analyzed in terms of percolation theory taking into account alloy scattering and spatial correlations of impurity centers.